M2 Macrophage-Based Prognostic Nomogram for Gastric Cancer After Surgical Resection - Hu, Jianwen; Ma, Yongchen; Ma, Ju; Yang, Yanpeng; Ning, Yingze; Zhu, Jing; Wang, Pengyuan; Chen, Guowei; Liu, Yucun (Frontiers in Oncology, 2021)
A good prediction model is useful to accurately predict patient prognosis. Tumor–node–metastasis (TNM) staging often cannot accurately predict prognosis when used alone. Some researchers have shown the infiltration of M2 macrophages in many tumors indicates poor prognosis. This approach has the potential to predict prognosis more accurately when used in combination with TNM staging, but there is less research in gastric cancer. A multivariate analysis demonstrated that CD163 expression, TNM staging, age, and gender were independent risk factors for overall survival. Thus, these parameters were assessed to develop the nomogram in the training dataset, which was test in the validation and whole datasets. The model showed a high degree of discrimination, calibration and good clinical benefit in the training, validation, and whole datasets. In conclusion, we combined CD163 expression in macrophages, TNM staging, age, and gender to develop a nomogram to predict three and five-year overall survival after curative resection for gastric cancer. This model has the potential to provide further diagnostic and prognostic value for patients with gastric cancer.